Validation of a protein panel for the noninvasive detection of recurrent non-muscle invasive bladder cancer. (3rd October 2017) - Gogalic, Selma; Sauer, Ursula; Doppler, Sara; Heinzel, Andreas; Perco, Paul; Lukas, Arno; Simpson, Guy; Pandha, Hardev; Horvath, Andras; Preininger, Claudia
Abstract: Context: About 50–70% of patients with non-muscle invasive bladder cancer (NMIBC) experience relapse of disease. Objective: To establish a panel of protein biomarkers incorporated in a multiplexed microarray (BCa chip) and a classifier for diagnosing recurrent NMIBC. Materials and methods: Urine samples from 45 patients were tested. Diagnostic performance was evaluated by receiver operating characteristic (ROC) analysis. Results: A multi biomarker panel (ECadh, IL8, MMP9, EN2, VEGF, past recurrences, BCG therapies and stage at diagnosis) was identified yielding an area under the curve of 0.96. Discussion and conclusion: This biomarker panel represents a potential diagnostic tool for noninvasive diagnosis of recurrent NMIBC.